Inhibition of Neurotoxic Secretory Phospholipases A(2) Enzymatic, Edematogenic, and Myotoxic Activities by Harpalycin 2, an Isoflavone Isolated from Harpalyce brasiliana Benth - Ximenes, Rafael M.; Rabello, Marcelo M.; Araujo, Renata M.; Silveira, Edilberto R.; Fagundes, Fabio H. R. [UNESP]; Diz-Filho, Eduardo B. S. [UNESP]; Buzzo, Simone C. [UNESP]; Soares, Veronica C. G. [UNESP]; Toyama, Daniela de O.; Gaeta, Henrique H. [UNESP]; Hernandes, Marcelo Z.; Monteiro, Helena S. A.; et al. (Hindawi Publishing Corporation, 2012)
Secretory phospholipases A(2) (sPLA(2)) exert proinflammatory actions through lipid mediators. These enzymes have been found to be elevated in many inflammatory disorders such as rheumatoid arthritis, sepsis, and atherosclerosis. The aim of this study was to evaluate the effect of harpalycin 2 (Har2), an isoflavone isolated from Harpalyce brasiliana Benth., in the enzymatic, edematogenic, and myotoxic activities of sPLA2 from Bothrops pirajai, Crotalus durissus terrificus, Apis mellifera, and Naja naja venoms. Har2 inhibits all sPLA(2) tested. PrTX-III (B. pirajai venom) was inhibited at about 58.7%, Cdt F15 (C. d. terrificus venom) at 78.8%, Apis (from bee venom) at 87.7%, and Naja (N. naja venom) at 88.1%. Edema induced by exogenous sPLA(2) administration performed in mice paws showed significant inhibition by Har2 at the initial step. In addition, Har2 also inhibited the myotoxic activity of these sPLA(2)s. In order to understand how Har2 interacts with these enzymes, docking calculations were made, indicating that the residues His48 and Asp49 in the active site of these enzymes interacted powerfully with Har2 through hydrogen bonds. These data pointed to a possible anti-inflammatory activity of Har2 through sPLA(2) inhibition.